Effect of Carrot Juice To Decrease The Primary Dysmenorrhea Pain on Adolescent Girls in Dorm Poltekkes Kemenkes Pontianak - Dini Fitri Damayanti; Sarah Aprilia; Emy Yulianti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Dysmenorrhea is pain during menstruation, usually with felt cramp and concentrated in the lower abdomen. Pain complaints from mild to severe. Based on the causes, dysmenorrhea was divided into two, namely primary and secondary dysmenorrhea. The method to treat dysmenorrhea was used painkillers, take a rest, take a deep breath, calm down, exercise lightly, eat vegetables and fruits, compress the pain parts with hot water. One of nonfarmacology method is use carrot juice. The purpose of this research is to find out carrot juice can reduce primary dysmenorrhea pain on adolescent girls in dorm Poltekkes Kemenkes Pontianak. This research was used the quasy experiment method with a pre and post test without control approach. The sampling technique was used purposive sampling. Data collections conduct from May to June 2019 used the NRS questionnaire, Sheet Procedure for Giving Carrot Juice. Data was analyzed by Wilcoxon test. The research results showed that before be given carrot juice, the middle value of primary dysmenorrhea pain was 6.00. After be given carrot juice, the middle value of primary dysmenorrhea pain was 2.00, which means there is a difference in pain around 4.00 and a value of p = 0,000 (p. 0.05). The conclusion is there are differences in the pain of primary dysmenorrhea before and after be given carrot juice.